LOG DATA ANALYSIS ON LOW RESISTIVITY RESERVOIR CASE IN Z FIELD FOR DETERMINATION OF PRODUCTIVE ZONE - Mohammad Barezzi Naufal Taftazzanni (Jurnal Eksakta Kebumian, 2021)
AbstractWell Logging is a job to get subsurface data. The anomaly on the results of reading log data is one of the cases that often occurs. Low resistivity reservoir is an example. In Field Z there were 6 wells studied. In these wells in the Telisa formation it is indicated that the reservoir zone has a low resistivity (1-7 Ωm). This is indicated by the existence of a good oil show, namely the presence of fluorescence, stain and cut for the six wells based on mud log data. However, based on log data, this zone has a low resistivity. This anomaly has caused this reservoir zone to be overlooked during the initial exploration period. Therefore, it is necessary to analyze the core data in the area indicated by low resistivity in order to find out the cause of the low resistivity value. The presence of clay minerals is the main factor causing low resistivity values. Based on XRD data, the composition of clay minerals in the research wells ranged from 11-47% including Smectite minerals, Illite minerals, kaolinite minerals and chlorite minerals. The conductive properties of clay minerals are the cause of the low resistivity value. In addition, based on the analysis of the shale distribution in the Telisa formation is a type of laminated shale. The presence of shale content in sandstone can bind water significantly (clay bound water) thus reducing the reading of the resistivity value. In addition to determining and analyzing the low resistivity reservoir zone, petrophysical calculations are also carried out. For the calculation of water saturation in this study carried out using three methods, namely the Indonesian method, Simandoux and Archie. Based on the results of the validation of water saturation calculations on core data, it was found that the Indonesian method is the best method that matches the value of water saturation, which are 59%, 56.1%, 60.2%, 59.4%, 61.1% and 62.3%.Keywords: Well logging, low resistivity, XRD, oil show, clay mineral